Etiquetado nutricional, una mirada desde los consumidores de alimentos (2014)
ABSTRACT: Nutritional labeling is a consumer’s tool when it comes to taking decisions about their nutrition, for the health maintenance and prevention of disease. Objective: to describe the association between sociodemographic variables, upon reading the labels and identify the consumer’s perception about nutritional labeling. Materials and methods: A triangulation of methods were used; from a quantitative methodology, descriptive study was conducted on a sample of 384 persons. From a qualitative methodology, a focalized ethnography approach was used, 30 interviews were conducted, and 20 observations at the time of the purchasing food. Results: An association was found of (p<0,005) between sociodemographic variables such as: gender, educational level, occupation and the lecture of the nutritional label. From a qualitative component, consumers have a low level of information on the nutritional label and the difficulty interpreting it. The selection and purchase of food is not based on a nutritional basis but rather on reasons such as taste or tradition. Conclusions: The lack of knowledge about nutritional labeling, does not contribute to the process of selection and purchase of food. Other aspects such as personal and cultural are what determine the purchasing decision of consumers.